PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING TIPE WORDWALL TERHADAP PEMAHAMAN IPS MATERI KERAGAMAN SUKU BANGSA DAN BUDAYA DI SD 020254 KOTA BINJAI - Ginting, Nurlia Br; Sitepu, Reva Wenita Br (JURNAL CURERE, 2023)
Difficulties in learning are still a scourge faced to achieve good learning outcomes. This was also experienced by students at SD 020254 Kota Binjai in the subject matter of ethnic and cultural diversity. So it is interesting to do research to overcome problems through the application of wordwall type game-based learning models in order to improve student learning outcomes. The purpose of this study was to analyze the effect of the wordwall type game based learning model and provide a comparison of the magnitude of the influence exerted by the wordwall type game based learning model when compared to conventional on the subject of ethnic and cultural diversity. In this study Quasy Experimental Designs were used in the form of Nonequivalent [pretest posttest] Control Groups Design (NCGD). The population used as the sample was all fifth grade students at SD 020254 Binjai City, consisting of 50 students. The data analysis used was the independent sample t-test and the calculation of the N-gain value with the help of SPSS 21. The results showed that there were differences resulting from the wordwall type game-based learning model using the lecture method with the results of the sample t-test analysis of 0 .01<0.05.